Superconformal field theories and cyclic homology - Eager, Richard (String-Math 2014, 2016)
One of the predictions of the AdS/CFT correspondence ist the matching of protected operators between a superconformal field theory and its holographic dual. We review the spectrum of protected operators in quiver gauge theories that flow to superconformal field theories at low energies.